2005
DOI: 10.1111/j.1745-7254.2005.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue distribution of 5-fluorouracil encapsulated by galactosylceramide liposomes in mice1

Abstract: Aim: To study the pharmacokinetics and tissue distribution of 5‐fluorouracil encapsulated by galactosylceramide liposomes (5‐Fu‐GCL) in mice. Methods: The concentration of 5‐fluorouracil (5‐Fu) in serum was detected by high performance liquid chromatography after 5‐Fu‐GCL (80, 40, 20 mg/kg) and free 5‐Fu (40 mg/kg) were injected intravenously into mice. The tissue distribution of 5‐Fu‐GCL (40 mg/kg) and free 5‐Fu (40 mg/kg) was investigated, and concentration‐time profile of the two preparations in the liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…In a single study examining 5-fluorouracil alone, four repeated injections of 150 mg/kg 5-fluorouracil failed to alter maze performance in young female rats (Lee et al 2006), a result in contrast to the present findings. The doses of 75 mg/kg (present study) and 150 mg/kg (Lee et al 2006) 5-fluorouracil in mice and rats, respectively, fall slightly below and slightly above the predicted 100-mg/kg-scaled mouse dose as determined from the typical clinical dose used to treat breast cancer in humans (500 mg/m 2 ) (Gusella et al 2006;Jin et al 2005;Kralovanszky et al 1999;Ooi et al 2001;Peters et al 1993). The findings in the present study underscore the importance of examining a range of relevant preclinical and clinical doses in more than one type of assay to capture the relationship of chemotherapeutic agents to changes in different types of learning and memory behaviors.…”
Section: Discussionmentioning
confidence: 40%
“…In a single study examining 5-fluorouracil alone, four repeated injections of 150 mg/kg 5-fluorouracil failed to alter maze performance in young female rats (Lee et al 2006), a result in contrast to the present findings. The doses of 75 mg/kg (present study) and 150 mg/kg (Lee et al 2006) 5-fluorouracil in mice and rats, respectively, fall slightly below and slightly above the predicted 100-mg/kg-scaled mouse dose as determined from the typical clinical dose used to treat breast cancer in humans (500 mg/m 2 ) (Gusella et al 2006;Jin et al 2005;Kralovanszky et al 1999;Ooi et al 2001;Peters et al 1993). The findings in the present study underscore the importance of examining a range of relevant preclinical and clinical doses in more than one type of assay to capture the relationship of chemotherapeutic agents to changes in different types of learning and memory behaviors.…”
Section: Discussionmentioning
confidence: 40%
“…Thomas et al (17) performed a PK study on non-PEGylated liposomes but did not calculate any PK parameters. Jin et al (46) evaluated the PK of galactosylceramide liposomes encapsulating 5-FU and found a shorter distribution half-life of 28 min and a 3 to 5-fold lower AUC of 38 μmol.h.L −1 . Our TSLs and NTSLs formulations are therefore better in terms of exposure.…”
Section: Discussionmentioning
confidence: 98%
“…However, increased circulation time can be accomplished by designing particles of smaller size or by coating the external membrane with specific ligands or proteins (Laquintana et al 2009). Surface-modified liposomes and nanoparticles have shown great promise in the treatment of brain tumor due to their ability to effectively cross the BBB and deliver therapeutic agents to the brain (Huwyler et al 2008, Jin et al 2005.…”
Section: Microcapsulesmentioning
confidence: 99%